DIFFERENCES OF ANTHROPOMETRICAL STATUS ON TOP LEVEL HANDBALL PLAYERS AND NON SPORTSMEN - Bojan Mašanović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
There are many researches about the differences of anthropometrical measures on sportsmen and non sportsmen. The object of this research is the relation of anthro- pometrical status on top level handball players and non sportsmen. The main goal of this research represents the derivation some knowledge about the difference of anthro- pometrical status on top level football players and non sportsmen. The sample involved 15 handball players who play in Handball club "Vojvodina" from Novi Sad and 31 non sportsmen. The variables involved 20 anthropometrical measures which define longitu- dinal and transversal measures of skeleton, volumes and physical size and skinfolds. The data was collected by t-test